Kapabilitas Membangun Jaringan dengan Pemasok untuk Meningkatkan Kinerja Operasional Pada Toko Aksesoris Telepon Genggam Di Kabupaten Banyumas - Sri Sundari; Cahyaningtyas Ria Uripi (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The increasing need for mobile phones has resulted in the rapid development of the mobile phone accessories business in Banyumas Regency. Competition between accessories stores results in the importance of operational performance in order to maintain its survival. To be able to achieve superior operational performance, a mobile phone accessories shop must have the capability to build a network with suppliers. This study aims to examine the effect of the capability of building a network with suppliers (consisting of three dimensions, namely developing effective network structures, supplier base reduction and longterm orientation) and supplier operational performance on the operational performance of mobile phone accessories stores.This research is a survey research with a population of mobile phone accessories stores in Banyumas Regency and a sample size of 100 respondents. The method of analysis and hypothesis testing uses the Structural Equation Model (SEM) using the AMOS 22 program. From the test results it can be concluded that developing effective network structures has a positive effect on supplier operational performance, Supplier base reduction has a positive effect on supplier operational performance, Longterm orientation has a positive effect on supplier operational performance. supplier operational performance, supplier operational performance has a positive effect on organization operational performance. The implication of this research is that there is a need to increase in establishing an effective network between mobile phone accessories stores and suppliers so that the operational performance of the business units increases.